Tacrolimus combined with arsenic trioxide provides a three-in-one drug-eluting coronary stent integrating anti-restenosis, pro-endothelialization and anti-inflammation - Yaojia Zhang; Hongchi Yu; Li Deng; Zhe Hou; Jie Yang; Fei Fang; Michael Z. Miao; Wenjun Li; Xin Shen; Dongyun Hao; Xiaoyi Ma; Lifeng Zhou; et al. (Medicine in Novel Technology and Devices, 2024)
The limitations of current drug-eluting stent technologies in selectively inhibiting vascular smooth muscle cell proliferation, which often leads to inflammation, call for innovative approaches in coronary artery disease treatment. In the present work, we propose a revolutionary solution: a three-in-one platform for vascular stents, combining arsenic trioxide (ATO) and tacrolimus (TAC) to address anti-proliferation, pro-endothelialization, and anti-inflammation aspects. Our findings demonstrate that the synergistic action of ATO and TAC effectively suppresses aberrant vascular smooth muscle cell proliferation and mitigates endothelial cell inflammation. Remarkably, the combination treatment of TAC/ATO enhances endothelial cell migration and adhesion abilities. Moreover, our TAC/ATO-eluting stent exhibits superior re-endothelialization and anti-restenosis effects in a rabbit and porcine stent implantation model. Both in vitro and in vivo results solidify the notion that the TAC/ATO-eluting stent ensures rapid re-endothelialization and significantly reduces the incidence of in-stent restenosis. Overall, this study represents a promising and novel multifunctional platform with immense potential in the therapy of coronary artery disease.